Vitamin D toxicity with acute kidney injury in siblings – a case report and literature review - Szawłoga, Tomasz; Sobieszczańska-Droździel, Aleksandra (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Vitamin D toxicity is a significant and increasingly diagnosed clinical issue. Despite clearly defined guidelinesw for the prevention and treatment of its deficiency, a growing trend of unsupervised high-dose supplementation is observed. We present two brothers who took 10,000 IU of cholecalciferol daily for over a month. One developed nonspecific symptoms of severe hypercalcemia (4.07 mmol/l) and acute kidney injury (eGFR 63), with serum 25(OH)D of 610 ng/ml. The other patient remained nearly asymptomatic despite a markedly elevated 25(OH)D level (501 ng/ml) and hypercalcemia (3.13 mmol/l). The applied treatment – glucocorticoids, forced diuresis, and electrolyte supplementation – caused normalization of calcemia and renal function. The presented case illustrates the broad spectrum of clinical manifestations associated with vitamin D toxicity and underscores the need to raise public awareness of the dangers linked to its excessive supplementation. It also emphasizes the importance of medical supervision when using vitamin D, particularly in children.